FDI Inflow in Indian Retailing - Growth Model and Challenges - Biswas, Supriya (Indian Journal of Marketing, 2010)
India is ranked as the most attractive retail destination among 30 emerging markets by the Annual Global Retail Development Index (GRDI) for two years consecutively (AT Kearney). It is the fifth largest as of 2009, recording an average growth of 10% annually, accounting for over 10 per cent of the country's GDP (India's GDP is 1.25 Trillion USD that is INR 55 Trillion in 2008-09) and around 8 per cent of the employment. One of the reasons behind such phenomenal attraction is because 47% of India's population is under 20 years of age contributing immensely to the growth of this sector. While examining the historical background, it becomes apparent that the government outlook towards FDI has been picking up considerable attention since the early 90s. During the 70s, Foreign Exchange Regulation Act (FERA) 1973 was enough to dissuade any foreign investment in the country and as a sequel to this act - on 1st June 1978, the bell tolled for MNC giants like IBM and Coke to pack off their operations from the Indian soil. FERA, repealed in 2000, had meanwhile lent some benefits that led to self-sufficiency and growth of domestic brands, financial sectors like banks and insurance. There were domestic FMCG majors like Thumbs up, Campa-Cola, Nirma, growth of nationalized banks and insurance companies that built a strong base in the domestic market with an outlook of economic and social development coupled with massive employment generation. Truly speaking, India Inc. reaped its benefit while 2008 witnessed severe global recession leading to millions of pink slips world wide, collapse of reputed financial institutions, like Lehman Brothers Holdings Inc. (US based premier global financial services firm). With its huge population, India could manage to survive the backlash of this recessional epidemic without acute suffering. But the other side of the story is equally grim and squalid: the 'closed door' economy damaged the competitive edge of 'Brand India' in the global market leading to economic and technical bankruptcy of our product and services in the international market.